Bilingual visual dictionary. (Bilingual visual dictionary., 2018)
With over 10,000 fully illustrated terms arranged by theme and an audio app, Russian language learning has never been easier. Perfect for tourist and business travellers alike, DK's Bilingual Visual Dictionary series is by your side when buying food, talking about work, discussing health, and studying language. Stunning visuals and comprehensive indexes combine to make the Russian English Bilingual Visual Dictionary your indispensable Russian language companion. Fully updated to reflect recent changes in technology and clothing, the Russian English Bilingual Visual Dictionary also features an easy-to-use free audio app available on the App Store and Google Play, enabling you to hear terms spoken out loud. Learn and retain all the key phrases you need to know, and perfect your pronunciation with audio help.